Cytochrome‐P450‐Induced Ordering of Microsomal Membranes Modulates Affinity for Drugs. (22nd February 2018) - Barnaba, Carlo; Sahoo, Bikash Ranjan; Ravula, Thirupathi; Medina‐Meza, Ilce G.; Im, Sang‐Choul; Anantharamaiah, G. M.; Waskell, Lucy; Ramamoorthy, Ayyalusamy
Abstract: Although membrane environment is known to boost drug metabolism by mammalian cytochrome P450s, the factors that stabilize the structural folding and enhance protein function are unclear. In this study, we use peptide‐based lipid nanodiscs to "trap" the lipid boundaries of microsomal cytochrome P450 2B4. We report the first evidence that CYP2B4 is able to induce the formation of raft domains in a biomimetic compound of the endoplasmic reticulum. NMR experiments were used to identify and quantitatively determine the lipids present in nanodiscs. A combination of biophysical experiments and molecular dynamics simulations revealed a sphingomyelin binding region in CYP2B4. The protein‐induced lipid raft formation increased the thermal stability of P450 and dramatically altered ligand binding kinetics of the hydrophilic ligand BHT. These results unveil membrane/protein dynamics that contribute to the delicate mechanism of redox catalysis in lipid membrane.